Liver Fibrosis and Metabolic Alterations in Adults With alpha-1-antitrypsin Deficiency Caused by the Pi*ZZ Mutation - Hamesch, Karim (2019)
BACKGROUND & AIMS: Alpha-1 antitrypsin deficiency (AATD) is among the most common genetic disorders. Severe AATD is caused by a homozygous mutation in the SERPINA1 gene that encodes the Glu342Lys substitution (called the Pi*Z mutation, Pi*ZZ genotype). Pi*ZZ carriers may develop lung and liver diseases. Mutation- associated lung disorders have been well studied, but less is known about the effects in liver. We assessed the liver disease burden and associated features in adults with this form of AATD. METHODS: We collected data from 554 Pi*ZZ adults (403 in an exploratory cohort, 151 in a confirmatory cohort), in 9 European countries, with AATD who were homozygous for the Pi*Z mutation, and 234 adults without the Pi*Z mutation (controls), all without pre-existing liver disease. We collected data on demographic parameters, comorbidities, lung- and liver-related health, and blood samples for laboratory analysis. Liver fibrosis was assessed non-invasively via the serum tests Aspartate Aminotransferase to Platelet Ratio Index and HepaScore and via transient elastography. Liver steatosis was determined via transient elastography-based controlled attenuation parameter. We performed histologic analyses of livers from transgenic mice that overexpress the AATD-associated Pi*Z variant. RESULTS: Serum levels of liver enzymes were significantly higher in Pi*ZZ carriers vs controls. Based on non-invasive tests for liver fibrosis, significant fibrosis was suspected in 20%–36% of Pi*ZZ carriers, whereas signs of advanced fibrosis were 9- to 20-fold more common in Pi*ZZ carriers compared to non-carriers. Male sex; age older than 50 years; increased levels of alanine aminotransferase, aspartate aminotransferase, or g-glutamyl transferase; and low numbers of platelets were associated with higher liver fibrosis burden. We did not find evidence for a relationship between lung function and liver fibrosis. Controlled attenuation parameter 280 dB/m, suggesting severe steatosis, was detected in 39% of Pi*ZZ carriers vs 31% of controls. Carriers of Pi*ZZ had lower serum concentrations of triglyceride and low- and very-lowdensity lipoprotein cholesterol than controls, suggesting impaired hepatic secretion of lipid. Livers from Pi*Zoverexpressing mice had steatosis and down-regulation of genes involved in lipid secretion. CONCLUSIONS: In studies of AATD adults with the Pi*ZZ mutation, and of Pi*Z-overexpressing mice, we found evidence of liver steatosis